Penerapan PjBL berbasis CRT sebagai upaya meningkatkan rasa ingin tahu (curiosity) dan motivasi belajar peserta didik - Naila Zulfa Ainuzzahroh; Fina Fakhriyah; Rizky Oktavian Saputra (Universitas Sebelas Maret, 2025)
This purpose of this research is to determine the effectiveness of the application of the Project Based Learning (PjBL) model with a Culturally Responsive Teaching (CRT) approach to increase students' curiosity and learning motivation. This study used the design of Classroom Action Research (PTK) model Kemmis and McTaggart which was carried out in two cycles. The research subjects were 32 third grade students at SD 1 Barongan Kudus. The data collection techniques used were observation & questionnaire. The data analysis technique uses quantitative descriptive analysis. The results showed an increase in students' curiosity by 24% (observation) and 23% (questionnaire), as well as an increase in learning motivation by 22% (observation) and 24% (questionnaire) from pre-cycle to cycle II. Thus, the application of the PjBL model with the CRT approach is effective in increasing students' curiosity and motivation to learn in learning mathematics gradually.